Nutritional evaluation of some Indian tree pods for livestock feeding - SANTRA, A; KARIM, S A (The Indian Journal of Animal Sciences, 2021)
The objective of this study was to evaluate promising tree pods for feeding to the livestock particularly for the small ruminants. Out of eight tested tree pods, seven tree pods, i.e. White siris (Albizia procera), Siris (Albizia lebbeck), White kheri (Acacia senegal), Babul (Acacia arabica), Khejri (Prosopis cineraria), Vilayati babul (Prosopis juliflora) and Sajna (Moringa oleifera) were collected from semiarid region of Rajasthan while one tree pods e.g., Jungle jalebi (Enterolobium timoba) was collected from Dehradun, Uttrakhand, India. Most of the tree pods were rich in CP content. On an average, OM, CP, EE, NDF, ADF and cellulose content of these tree pods were found to be 91.1, 16.7, 2.5, 43.3, 34.7 and 25.4% on DM basis, respectively. Rumen protozoal number decreased due to inclusion of Enterolobium timoba tree pods in the incubation media. The TVFA and propionate production were higher for Acacia Senegal, Acacia arabica tree pods followed by Moringa oleifera tree pods while ammonia nitrogen concentration was lower due to inclusion of Enterolobium timoba tree pods in the incubation media. All the tested tree pods had no effect on xylanase, Î²-glucosidase and amylase enzyme activity. However, specific activity of carboxymethyl cellulase enzyme reduced due to addition of Enterolobium timoba tree pods in the incubation medium. Highest IVDMD was observed for Acacia arabica tree pods followed by Acacia senegal and Moringa oleifera tree pods. The results indicated that Acacia arabica, Acacia senegal and Moringa oleifera are good tree pods for feeding to the animals.